Business Feasibility Study on The Bolu Cukke Home Industry Business In Lajoa Soppeng Regency - Wahyuni, Wahyuni; Rizal S, Muh; Didin, Didin (Pinisi Business Administration Review, 2023)
The results of this study indicate that (1) The description of the Bolu Cukke Home Industry business in Lajoa from 1989 until now has developed well, seen from the Bolu Cukke enthusiasts who are not only from the surrounding community but many are from outside the region. Currently, traditional food sponge cake has been used as a typical food of Lajoa, Jennae Village, especially Soppeng Regency (2) Home Industry Bolu Cukke in Lajoa is declared feasible because it has fulfilled aspects according to business feasibility study analysis such as aspects of legality, financial aspects, technical aspects of production, management and organizational aspects, socio-economic aspects, environmental impact aspects, but in terms of market and marketing aspects are not optimal both online and offline (3) Supporting factors Raw materials for home industry sponge cake in Lajoa Jennae Village, Liliriaja District, Soppeng Regency such as in terms of the price affordable, strategic location and create jobs. As for the inhibiting factors, such as the marketing process that does not reach the broad market due to the absence of the application of modern technological tools.